Sunflower seed hull: Its value as a broad mushroom substrate - Figlas, Norma Débora (2016)
Sunflower (Heliantus annus) seed hull (SSH), an abundant and cheap lignocellulosicresidue from edible oil-seed industries, was evaluated as an alternative substrate formushroom cultivation. Different edible and medicinal mushroom species were grownsuccessfully, bringing a positive use of material that could be problematic for disposal.In this review we display different studies that linked the SSH with mushroom productionand other derivations of its use as mushroom substrate.